Associação da ocorrência de formigas (Hymenoptera: Formicidae) com atributos do solo e da vegetação em um domínio do cerrado à nordeste do estado do maranhão, Brasil - Silva, Edison Fernandes da [UNESP] (2014)
Ants live in tree tops and shrubs, with many species using the soil/litter interface for foraging and other are resident in the soils. In this study proposes to identify species of ants in an area of the Cerrado Northeastern State of Maranhao and correlate the occurrence of ants with attributes of soils, vegetation, moisture and temperature at ground level. The study was conducted in the municipality of Chapadinha-MA in six environments: E1 and E2 Typical Dystrophic Oxisol, E3 Entisol Typical Dystrophic, E4 Petroplíntico Dystrophic Oxisol, E5 Paludalf Dystrophic Ultisol and E6 Plinthosol Petrico Êndico Litoplíntico. The characterization of the vegetation was carried out by phytosociological survey in 40 x 40 m plots. To evaluate the physical and chemical properties of the soils we collected disturbed soil samples and preserved structure in 0,0 - 0,1 m, 0,1 - 0,2 m and 0,2 - 0.3 m layers. The ants were collected with protein and a carbohydrate baits (sardines and honey) using nine pairs of baits distributed in the 40 x 40 m plots from six environments. To collect the ants in each plot the baits were observed individually for one hour (08:00 and 11:00 am) and the ants who accessed the baits were monitored and collected directly at the entrance of their nests. The dry biomass of litter was obtained in 1 m2 plots randomly distributed in 40 x 40 m plots. Humidity and temperature were obtained with hygrometer placed directly on the soil surface from the sampling environments. Descriptive statistical analysis and Principal Component Analysis (PCA) was carried out in the physical and chemical soil attributes. Ten ant species with higher importance value (HIV) were used in the PCA analysis. These species were correlated with soil attributes, litter biomass, basal area, humidity and temperature at ground level. Forty eight species from 7 subfamilies and 24 genera have been found. Nine species were restricted to records environments: E1 and ...